Utilization of Adolescent-Friendly Health Services (PKPR) From the Perspective of Andersen’s Behavioral Model at Four Primary Health Centers in Bone Bolango Regency: IN PRESS - Zulkifli Walangadi; Sry Ade Muhtya Gobel; Muamar Afdhal Mahendra; Luthfiana Nur; Nurul Anisa; Siti Qomaria Usu (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Adolescence is a critical developmental stage marked by increased vulnerability to reproductive health problems. However, evidence remains limited regarding the simultaneous contribution of Andersen’s predisposing, enabling, and need factors, together with adolescent-specific service characteristics and peer support, to the utilization of Adolescent-Friendly Health Services (PKPR) in local primary care settings. This study examined factors associated with PKPR utilization among adolescents in Bone Bolango Regency using Andersen’s Behavioral Model. A cross-sectional study was conducted in 2024 among 130 adolescents aged 15–19 years with previous primary health center service contact in the catchment areas of four primary health centers through proportional stratified and systematic random sampling. PKPR utilization was determined from primary health center records and categorized as ever or never utilized during the previous 12 months. Data were analyzed using multivariable binary logistic regression. The final model identified knowledge about PKPR (aOR = 3.809; 95% CI: 1.190-12.190), perceived need (aOR = 3.623; 95% CI: 1.299-10.106), provider preference (aOR = 4.646; 95% CI: 1.107-19.507), assessment of facilities (aOR = 3.936; 95% CI: 1.295-11.963), suitability of operating hours (aOR = 13.972; 95% CI: 3.810-51.238), and peer support (aOR = 3.756; 95% CI: 1.305-10.808) as factors independently associated with PKPR utilization. Sociodemographic characteristics and distance were not significantly associated with utilization. These findings support integrated interventions that strengthen adolescent health education, provide private and confidential counseling facilities, adjust service hours to adolescents’ schedules, improve provider responsiveness, and develop peer-supported outreach to increase PKPR utilization.